Beyond the wall : an investigation into the relationship between industrial design and science fiction : a thesis presented in partial fulfilment of the requirement of the degree of Master of Design, Massey University, Wellington, New Zealand - Garrett, Lyn Karena (Massey University, 2006)
The study aimed to develop a theory describing the nature of the relationship between industrial design and science fiction, based on the observation that science fiction caninspire industrial designers and enrich industrial design processes and products. The hypotheses were that: 1. The roles of industrial design and science fiction are based on parallel ideas. 2. Industrial design is suffused with, and sympathetic to, science fiction thinking. 3. There is a ‘cause and effect’ relationship between aspects of industrial design and science fiction. Science fiction cinema is a key ‘cause and effect’. 4. Science fiction cinema performs a key function in the roles of science fiction, and cinema can be employed to explore and discuss the roles of industrial design and science fiction. The study used a range of research methods. An extensive literature review critically compared and analysed the characteristics and roles of science fiction and industrial design. The analysis identified contrasting and common themes, ideas, processes, texts and subtexts between the two areas. The findings were further analysed using graphic analytical tools, to form models that described and structured the industrial design/science fiction relationship. Three case studies were used to further test the model: the work of industrial designer and visual futurist Syd Mead; science fiction author Bruce Sterling; and the industrial design and production design content of selected science fiction films. Analysis of an Internet discussion among industrial designers also illuminated the model. The findings from the analysis and the case studies supported the validity of the original hypotheses. The study identified as the key elements of an emerging theory the parallel ideas of innovation in industrial design and novum (the new thing) in science fiction; the cause and effect relationship found between the two disciplines; the parallel concepts of mediation and responsibility in industrial design, and anticipation and interrogation in science fiction. The theory was presented as a graphic model that demonstrated these elements. This study concludes that science fiction challenges the design profession to produce better design by requiring that social, political, and technological contexts in which products will exist are explicitly understood and addressed. This is mapped out in an emerging theory that outlines a complex, multi-layered relationship between industrialdesign and science fiction. In industrial design terms, this emerging theory could be considered a prototype.
Keywords: Industrial design; Science fiction; Emerging theory; Science fiction cinema; Production design; Forecasting; Fields of Research::410000 The Arts